2006
DOI: 10.1093/jn/136.6.1636s
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfur-Containing Amino Acids: An Overview

Abstract: Methionine, cysteine, homocysteine, and taurine are the 4 common sulfur-containing amino acids, but only the first 2 are incorporated into proteins. Sulfur belongs to the same group in the periodic table as oxygen but is much less electronegative. This difference accounts for some of the distinctive properties of the sulfur-containing amino acids. Methionine is the initiating amino acid in the synthesis of virtually all eukaryotic proteins; N-formylmethionine serves the same function in prokaryotes. Within pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
703
1
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 929 publications
(724 citation statements)
references
References 22 publications
5
703
1
15
Order By: Relevance
“…Thus, we cannot exclude the possibility that methionine, through the conversion to SAM, regulates Na/K-ATPase-mediated blastocoelic cavitation, as suggested by Bonilla et al [9]. Furthermore, the impaired blastocyst development induced by ethionine was not completely recovered by SAM, suggesting that SAM-independent roles of methionine such as a source of protein synthesis are also important in bovine blastocyst development [1,2]. Importantly, the results of the present study indicate that disruption of methionine metabolism is critical for development after zygotic gene activation (ZGA), which is considered to occur at the 8-cell stage in the case of bovine [39,40].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, we cannot exclude the possibility that methionine, through the conversion to SAM, regulates Na/K-ATPase-mediated blastocoelic cavitation, as suggested by Bonilla et al [9]. Furthermore, the impaired blastocyst development induced by ethionine was not completely recovered by SAM, suggesting that SAM-independent roles of methionine such as a source of protein synthesis are also important in bovine blastocyst development [1,2]. Importantly, the results of the present study indicate that disruption of methionine metabolism is critical for development after zygotic gene activation (ZGA), which is considered to occur at the 8-cell stage in the case of bovine [39,40].…”
mentioning
confidence: 85%
“…Dev. 58: [91][92][93][94][95][96][97] 2012) M ethionine is a dietary essential amino acid that plays multiple biological roles, including those as the initiating amino acid in eukaryotic protein synthesis, a precursor of the essential methyl donor for methylation reactions (S-adenosylmethionine, SAM) and a source of redox regulators (cysteine and glutathione) [1,2]. Methionine metabolism can be seen as the trans-and remethylation cycle of methionine (methionine cycle) that intertwines with the cycle of folate metabolism (folate cycle) and the transsulfuration pathway from homocysteine, an intermediate in the methionine cycle [3], and these combined metabolic networks are called one-carbon metabolism [4,5].…”
mentioning
confidence: 99%
“…Methionine is an indispensable amino acid and is transmethylated intracellularly to homocysteine via S-adenosylmethionine (SAM), an important methyl donor for most biological methylation reactions (1). Homocysteine can be further catabolized to cysteine through transsulfuration, which is regulated by the enzymes cystathionine ␤-synthase (CBS) (EC 4.2.1.22) and cystathionine ␥-lyase (EC 4.4.1.1).…”
mentioning
confidence: 99%
“…It is suggested that about 30% of the dietary SAA is utilised by the gut for epithelial cell differential and mucosal growth (BauchartThevret et al 2009). Furthermore, available literature indicated that SAA could stimulate humoral and cellmediated immune responses and the metabolites from Met possess pro-and anti-inflammatory properties (Hunter & Grimble 1994;Brosnan & Brosnan 2006). The feeding programmes without in-feed antibiotic may alter the SAA requirement for optimal performance.…”
Section: Introductionmentioning
confidence: 99%